Identifying and characterizing the most heavily dust-obscured galaxies at 1 ≤ z ≤ 4. Issue 4 (29th November 2022) - Martis, Nicholas S; Marchesini, Danilo M; Muzzin, Adam; Willott, Chris J; Sawicki, Marcin
ABSTRACT: We present 65 extremely dust-obscured galaxies from the UltraVISTA DR3 survey of the COSMOS field at 1 < z < 4. In contrast to other studies of dusty galaxies, we select our sample based on dust attenuation measured by UV–MIR spectral energy distribution (SED) modelling that allows for extreme attenuation levels. We construct our sample by making cuts at 1 ≤ z ≤ 4, A V ≥ 3, and log( M * /M⊙ ) ≥ 10.5. This method reliably selects galaxies exhibiting independent indicators of significant dust content, including far-infrared detection rates. We perform panchromatic SED modelling with matched Herschel photometry and find stellar and dust properties that differ from typical submillimetre galaxy (SMG) samples as well as Herschel sources matched in redshift and stellar mass. Our sources have lower star formation rates and higher AV than SMGs, but comparable total infrared luminosities. Most of our sample falls on or near the star-forming main sequence for this redshift range. Finally, we perform a morphological analysis with galfit using the KS -band images and Hubble F 814 W and F 160 W imaging when available. Typical axial ratios of ∼0.4 suggest disc-like morphology for the majority of our sources, and we note only three apparent merging systems. Our sample generally agrees with the size–mass relation for star-forming galaxies, with a tail extending to smaller sizes. We conclude that the most heavily obscured galaxies in this redshift range share many characteristics with typical star-forming galaxies, forming a population of dusty galaxies that overlaps, but is not encompassed by, those selected through dust emission.